Determinan Kualitas Laporan Keuangan dengan Moderasi Permenkop UKM 13 Tahun 2015 - Intan Milania; Anantawikrama Tungga Atmadja; Edy Sujana (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
The research conducted on this occasion was used by researchers to determine the influence of several variables which include: (1) understanding of accounting, (2) use of information technology, (3) HR competency on the quality of financial reports which in this research is moderated using implementation of the Minister of Cooperatives Regulation. This research has been supported by population data, namely all cooperatives in the Gianyar Regency area with data reaching 1,285 units. In carrying out the sampling process, this research used a purposive sampling technique, so that sample data was successfully obtained with a total of 171 cooperatives. The researchers have chosen a data collection technique using the process of distributing questionnaires. The data successfully obtained by the researchers will continue to be processed with the support of the SEM PLS version 4.0 application. The results of this research succeeded in providing proof that understanding accounting and also the use of information technology produces a positive and significant influence on the quality of financial reports, while the HR competency variable does not produce a significant influence on the quality of cooperative financial reports. Keywords: report quality, accounting, technology, competence